PERINGKAT JARAK METRIK PADA BILANGAN KABUR SEGITIGA UNTUK MENYELESAIKAN MASALAH PROGRAM PECAHAN LINIER KABUR - PERTIWI PUTRI ANDINI (Jurnal Matematika, 2015)
ABSTRAK : Fuzzy linear fractional programming problem (FLFPP) is general form of Fuzzy linier programming (FLPP) problem. FLFPP can be solved by not changing the fuzzy data become crisp on the objective function and the main state. Numbers are used in fuzzy linear programming is a triangular fuzzy numbers. In this thesis learned methods that have been developed by Al. Nachammai dan P. Thangaraj for solving FLFPP problem in triangular fuzzy number using metric distance ranking. From case studies are given, obtained metric distance ranking method on triangular fuzzy number is the appropriate method to resolve FLFPP problem because this method can show the maximum results.Keywords: Triangular Fuzzy Number, Metric Distance Ranking, Fuzzy Linear Programming, Fuzzy Linear Fractional Programming